Análise numérica de pilares mistos de seção quadrada preenchidos com concreto e submetidos à flexo-compressão - Melo, Ruan Aparecido de (2018)
The steel-concrete composite columns are characterized by the combination of steel profiles and structural concrete to form a single, tough section. Among the composite columns, the one of the filled type stands out, characterized by the filling of the tubular profile of steel by concrete. In this system, the combination of steel and concrete aims to take advantage of the good characteristics of these materials in a single structural element besides imparting speed of execution, flexibility, freedom in structural design, lightness, compatibility with other materials and rational use of materials. In this context, the present work presents the development of a methodology for numerical analysis of the square concrete filled steel tube composite columns under eccentric loads. For the modeling, the software ANSYS® was used and the numerical model was validated using experimental results. Important aspects of the choice of finite elements, mesh and form of force application, as well as the constitutive models of steel and concrete were discussed. After validation, the numerical model was used to evaluate the influence of the yielding strength of steel and the concrete compression, eccentricity of the applied force and slenderness ratio in the load resistance and the behavior of the concrete filled steel tube column. The analyzed parameters revealed a direct influence on the behavior of the concrete filled steel tube column mainly in terms of load capacity and rigidity. Comparative analyzes of all parameters allowed observations on the most important variables.